Pengembangan Media Powerpoint Interaktif Pada Materi Keragaman Budaya - Kumala Sari, Ernita; Fitriyeni (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The aim of this research is to develop interactive PowerPoint learning media on class 4 cultural diversity material, making it easier for teachers to deal with students who lack focus in learning. This research method uses development research with the ADDIE development model. The DDIE development design consists of 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. However, this research was only carried out in three stages, namely 1) the analysis stage consisting of analysis of educators, students and learning materials; 2) the design stage, namely the preparation of interactive PowerPoint learning media using the PowerPoint application; 3) development stage, namely producing learning media that has been designed at the design stage; 4) implementation stage, namely the trial stage carried out on students; 5) evaluation stage, namely the stage where revisions are made after receiving suggestions, comments and input from teachers, students and validators. Apart from production media, researchers also prepared research instruments, namely validation sheets. The validation sheet was filled in by 6 expert validators consisting of 2 media expert validators, 2 language expert validators, and 2 material expert validators. The results of this research show that interactive PowerPoint learning media meets the criteria for being very valid, with an average score of 89.1% from validators. Keywords: Learning Media; Interactive Power Point; Elementary school